Longitudinal Respiratory Subphenotypes and Differences in Response to Positive End-Expiratory Pressure and Fio2 Ventilation Strategy in COVID-19 ARDSTake-Home Points - Robin L. Goossen, MD; Daan F.L. Filippini, MD; Relin van Vliet, MD; Laura A. Buiteman-Kruizinga, RN, PhD; Markus W. Hollmann, MD, PhD; Sheila N. Myatra, MD; Ary Serpa Neto, MD, PhD; Peter E. Spronk, MD, PhD; Meta C.E. van der Woude, MD, PhD; Marcus J. Schultz, MD, PhD; David M.P. van Meenen, MD, PhD; Frederique Paulus, PhD; et al. (CHEST Critical Care)
Background: In patients with ARDS, positive end-expiratory pressure (PEEP) titration remains a challenge and recommendations are not in agreement. In mechanically ventilated patients with COVID-19, subphenotypes based on different respiratory trajectories have been identified, but their heterogeneity in response to PEEP/Fio2 strategy remains understudied. Research Question: Can these previously determined subphenotypes be detected early in the course of mechanical ventilation, and do these subphenotypes moderate the association between PEEP and Fio2 ventilation strategy and mortality? Study Design and Methods: Retrospective analysis of invasively ventilated patients with COVID-19. Patients were categorized into 2 treatment groups: high PEEP/low Fio2 strategy and low PEEP/high Fio2 strategy. To replicate previously described longitudinal respiratory subphenotypes, hereafter named the low-power or high-power subphenotype, a prediction model was created. The primary outcome was the interaction between PEEP/Fio2 strategy and subphenotype, with mortality as the dependent variable. Results: Of the 1,464 patients included in this analysis, 361 patients (25%) were allocated into the high PEEP/low Fio2 strategy and 1,103 patients (75%) were allocated into the low PEEP/high Fio2 strategy. A prediction model consisting of respiratory data of the first 2 days of invasive ventilation (area under the receiver operating characteristics curve, 0.88) assigned 908 patients (62%) to the low-power subphenotype and 556 patients (38%) to the high-power subphenotype. The high-power subphenotype was characterized by higher minute volume, mechanical power, ventilatory ratio, and driving pressure. The association between PEEP/Fio2 ventilation strategy and ICU mortality was moderated by the subphenotype (P = .03), with high PEEP/low Fio2 ventilation being associated with lower mortality in the low-power subphenotype (OR, 0.46; 95% CI, 0.31-0.67; P < .001) and not in the high-power subphenotype (OR, 0.85; 95% CI, 0.57-1.28; P = .44). Interpretation: In this study, high PEEP/low Fio2 ventilation was associated with improved mortality only in one of the subphenotypes, suggesting that such subphenotypes influence heterogeneity of PEEP and Fio2 effect and should be considered in personalized ventilation strategies. Clinical Trial Registry: ClinicalTrials.gov; No.: NCT05954351; URL: www.clinicaltrials.gov